Literasi Santri-Mahasiswa Universitas Islam Tribakti Lirboyo Kediri: Eksistensi, Karakteristik dan Tantangan - Andriawan, Didik; Surur, Aziz Miftahus; Amalia, Filda; Sulvadia, Syilvia Melinda; Rusyda, Atina (IIQ An Nur Yogyakarta, 2024)
This article discusses the existence, characteristics and challenges of digital literacy, focusing on the results of research on UIT Lirboyo Kediri santri-students. Digital literacy is an actual theme that is widely researched about measuring and examining the phenomenon of digital literacy in society. One thing that needs to be targeted for research is the digital literacy of students. Research on this theme is important to see the phenomenon of digital literacy in Islamic boarding schools. This research focuses on several things, (1) existence, (2) characteristics, and (3) challenges of digital literacy among santri-students. The method used in this research is qualitative, with informants from students as the primary source and central object of research. This research found that digital literacy among santri-students is quite strong and varied, especially related to things that are the duties of a santri who is also a college student, such as the need to fulfil assignments. The characteristics of student digital literacy are also quite varied, such as efficient and appropriate values, explorative, communicative and skill processing.